The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1152/ajpregu.1998.275.6.r1858
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate in the nucleus of the solitary tract activates both ionotropic and metabotropic glutamate receptors

Abstract: Glutamate is the proposed neurotransmitter of baroreceptor afferents at the level of the nucleus of the solitary tract (NTS). Blockade of ionotropic glutamate receptors with kynurenic acid blocks the arterial baroreflex but, paradoxically, does not abolish the response to exogenous glutamate. This study tested the hypothesis that exogenous glutamate in the NTS activates both ionotropic and metabotropic glutamate receptors (mGluRs). In urethan-anesthetized rats, unilateral microinjections of glutamate into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 18 publications
4
58
0
Order By: Relevance
“…Consistent with this explanation are the reports that bilateral blockade of glutamate receptors in the NTS are necessary to increase the baseline BP (24). Furthermore, blockade of ionotropic as well as metabotropic glutamate receptors in the NTS may be necessary to elevate baseline BP (11). We have previously shown that the concentrations of D-AP7 and NBQX used in this study are sufficient to block the responses to ionotropic glutamate-receptor agonists NMDA and AMPA, respectively (9,34).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with this explanation are the reports that bilateral blockade of glutamate receptors in the NTS are necessary to increase the baseline BP (24). Furthermore, blockade of ionotropic as well as metabotropic glutamate receptors in the NTS may be necessary to elevate baseline BP (11). We have previously shown that the concentrations of D-AP7 and NBQX used in this study are sufficient to block the responses to ionotropic glutamate-receptor agonists NMDA and AMPA, respectively (9,34).…”
Section: Discussionsupporting
confidence: 85%
“…However, other authors have also made similar observations. For example, blockade of ionotropic glutamate receptors by unilateral microinjections of kynurenic acid into the NTS did not elicit a significant increase in baseline BP (11). Perhaps compensatory mechanisms in the contralateral NTS prevent the baseline BP from rising.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effective dose and specific effect of Kyn on ionotropic glutamate receptors have been shown previously. 33 Bilateral microinjection of Kyn (0.15 to 5.0 nmol) into the PVN had no significant effect on the LSNA, MAP, and HR in 6 WKY rats. However, bilateral microinjection of Kyn (0.15 to 5.0 nmol/50 nL) into the PVN decreased the LSNA, MAP, and HR in 6 SHRs in a dose-dependent fashion ( Figure 5).…”
Section: Effect Of Microinjection Of Kyn Into the Pvnmentioning
confidence: 89%
“…We subsequently determined the effect of blockade of both NMDA and non-NMDA receptors by Kyn 15,27,33 in the PVN on sympathetic vasomotor tone in WKY rats and SHRs. The effective dose and specific effect of Kyn on ionotropic glutamate receptors have been shown previously.…”
Section: Effect Of Microinjection Of Kyn Into the Pvnmentioning
confidence: 99%